Heat transfer enhancement in microchannel heat sinks using mxene-based nanofluids: A CFD approach - Mohamad Nur Hidayat, Mat; Nurizzatul Atikha, Rahmat; Noor, M. M.; Eliza, M. Yusup; Muhammad Noor Afiq Witri, Muhammad Yazid; Nofrizalidris, Darlis (Penerbit UTHM, 2025)
As advancements in electronic technologies continue, the need for effective thermal management becomes increasingly vital. This research investigates the application of MXene-enhanced nanofluids at different volume concentrations in microchannel heat sinks to enhance cooling efficiency in electronic devices. Using numerical simulations based on a Eulerian multiphase framework, the study analyses the behavior and thermal properties of these nanofluids. Volume fractions ranging from 0.01% to 0.04% were assessed, and simulation results were cross validated with experimental data to ensure accuracy. At a Reynolds number of 300, a nanofluid concentration of 0.04 vol.% demonstrated a 20.1% decrease in thermal resistance when compared to water. Meanwhile, at Re 1000, the heat transfer coefficient improved by 29.4%. These outcomes indicate the promising potential of MXene-based nanofluids as advanced coolants for electronic heat sinks. The insights from this study are relevant across various electronic applications, such as power electronics, LEDs, and integrated circuits, and may support the design of superior cooling solutions for domains like aerospace, high-performance computing, and automotive electronics.